Clofazimine as a Treatment for Multidrug-Resistant Tuberculosis: A Review - Rhea Veda Nugraha; Vycke Yunivita; Prayudi Santoso; Rob E. Aarnoutse; Rovina Ruslami (Scientia Pharmaceutica, 2021)
Multidrug-resistant tuberculosis (MDR-TB) is an infectious disease caused by Mycobacterium tuberculosis which is resistant to at least isoniazid and rifampicin. This disease is a worldwide threat and complicates the control of tuberculosis (TB). Long treatment duration, a combination of several drugs, and the adverse effects of these drugs are the factors that play a role in the poor outcomes of MDR-TB patients. There have been many studies with repurposed drugs to improve MDR-TB outcomes, including clofazimine. Clofazimine recently moved from group 5 to group B of drugs that are used to treat MDR-TB. This drug belongs to the riminophenazine class, which has lipophilic characteristics and was previously discovered to treat TB and approved for leprosy. This review discusses the role of clofazimine as a treatment component in patients with MDR-TB, and the drug’s properties. In addition, we discuss the efficacy, safety, and tolerability of clofazimine for treating MDR-TB. This study concludes that the clofazimine-containing regimen has better efficacy compared with the standard one and is also well-tolerated. Clofazimine has the potential to shorten the duration of MDR-TB treatment.